STATE'S READINESS MOBILITY IN APPLYING NUCLEAR TECHNOLOGY AS ENERY DEVELOPMENT IN LEGAL PERSPECTIVE - Shatat, Shaleh Raed; Ariyana, Ade Riusma; Arifani, Devina (Jurnal Pembaharuan Hukum, 2021)
The states Nuclear Program is a program to build and utilize nuclear science and technology both in the non-energy sector and in the energy sector for peaceful purposes. Utilization of non-energy in Indonesia has developed quite advanced. The use of nuclear power in every countries covers various fields such as health, research and industry. Indonesia's readiness in implementing nuclear energy is carried out by ratifying international conventions, issuing laws, and issuing regulations from the Nuclear Energy Supervisory Agency, readiness in the field of infrastructure used to strengthen technology, and in Indonesia is committed to reducing 26% of greenhouse gas emissions in the year 2020. A nuclear power plant or nuclear power plant is a thermal power plant that uses one or more nuclear reactors as a heat source. The working principle of a nuclear power plant is almost the same as a steam power plant, using high pressure steam to turn a turbine. The rotation of the turbine is converted into electrical energy. The difference is the heat source used to generate heat. A nuclear power plant uses uranium as its heat source. The fission reaction (fission) of the uranium nucleus produces enormous heat energy. The power of a nuclear power plant ranges from 40 MWe to 2000 MWe, and a nuclear power plant built in 2005 has a power distribution from 600 MWe to 1200 MWe. As of 2015 there are 437 nuclear power plants operating in the world, which in total generate about 1/6 of the world's electrical energy. To date, around 66 nuclear power plants are being built in various countries, including China with 28 units, Russia with 11 units, India with 7 units, the United Arab Emirates with 4 units, South Korea with 4 units, Pakistan and Taiwan with 2 units each. Nuclear power plants are categorized based on the type of reactor used. However, in some plants that have several separate reactor units, it is possible to use reactor types that are fueled such as Uranium and Plutonium.